PEMBERDAYAAN KELOMPOK BUDIDAYA IKAN BANDENG BERBASIS IOT DI KELURAHAN TAPA’AN PASURUAN - Ernawati, Ernawati; Saputro, Cahyo Bagus; Sirot, Sayyid Agil; Ayu, Nyawijining Tita; Hidayati, Novi Itsna; Maghfiroh, Khoirin (Abdi Panca Marga, 2024)
Tapa'an Village is a coastal area in Bugul Kidul District, Pasuruan City, which has potential in the fisheries sector, one of the potential fishery products is milkfish. Management of pond water quality is crucial in milkfish cultivation. One management technique is to check pond water quality regularly. Pond water quality can be disturbed or degraded due to various factors. Cultivators usually carry out monitoring using traditional methods and not regularly. Therefore, to get good and optimal milkfish products, it is necessary to use instrumentation technology known as the internet of things (IoT). The aim of this activity is to provide understanding to fish farmers in Tapa'an regarding the application of IoT in optimizing milkfish cultivation. The activity started from the preparation stage, technical guidance, training and mentoring which was attended by the milkfish cultivator group, PKK Activation Team, Village Apparatus, Yudharta Pasuruan University KKN student group, and resource persons from the East Java Provincial Fisheries Service. The survey results obtained after the Bimtek conducted showed an increase in understanding of the material provided in the range of 80% - 100%. The highest percentage level of understanding after Bimtek was in the material on seed selection and feed selection reaching 100%, while the lowest was on knowledge of the benefits of IoT and its application in fish farming at 80%. References Aneta, A., & Sahami, F. M. (2021). Pelatihan Pengolahan Ikan Malalugis (Decapterus macarellus) Kepada Ibu-Ibu Pkk Desa Tihu Kecamatan Bonepantai Kabupaten Bone Bolango Malalugis Fish (Decapterus macarellus) Processing Training To the Family Welfare Empowerment Organization ( PKK ) in Tihu . Panritta Abdi, 5(3), 466–474. Annisa dan Lamusa, 2014. Analisis Kelayakan Usaha Tambak Bandeng di Desa Dolago Kecamatan Parigi Selatan Kabupaten Parifi Moutong. J Agrotekbis 2(3): 337-342 Anonim. 2001. Peraturan Pemerintah Republik Indonesia No. 82 Tahun 2001 tentang pengendalian pencemaran air. Kementrian sekretariat negara republik indonesia. Jakarta. Badan Standarisasi Nasional (BSN). 2013. Ikan Bandeng (Chanos-chanos Forsskal) – Induk Ikan Bandeng, SNI 01.6148.1999. Jakarta: Badan Standardisasi Nasional. Dewi, P. S., & Widiyawati, I. (2019). Pengenalan Teknologi Budidaya Tanaman Obat sebagai Upaya Pemanfaatan Lahan Pekarangan di Kelurahan Pabuwaran Purwokerto, Jawa Tengah. Jurnal Panrita Abdi, 3(2), 107–111. Ekawati, N. (2017). Parameter Air , Produksi dan Pendapatan Tambak Bandeng Sivofishery dan Non Silvofisheries di Kabupaten Cilacap. Jurnal Akuatika Indonesia Vol. 2 No. 1, 11. Firmansyah, M. (2020). Studi Kualitas Air Untuk Budidaya Ikan Bandeng (Chanos chanos Forsskal) Di Tambak Kelurahan Samataring Kecamatan Sinjai Timur. Jurnal Agrominansia, 5 (1), 106. Hidayaturrahmah 2007 . Waktu Motilitas dan Viabilitas ikan Mas (Cyprinus carpio L) pada Beberapa Konsentrasi Larutan Fruktosa. Bioscientiae. Vol. 4. 9-18. Huniyah A, Alamsjah MA, dan Pursetyo KT. 2015. Analisis Finansial Pembesaran Ikan Bandeng (Chanos chanos) Pada Tambak Tradisional Dengan Sistem Monokultur Dan Polikultur Di Kecamatan Mulyorejo, Surabaya, Jawa Timur. Jurnal Ilmiah Perikanan dan Kelautan. Vol. 7 No. 2, November 2015. Indah A, M dan Afandi. 2019. Analisis Pendapatan Usaha Tambak Bandeng di Desa Lalombi Kecamatan Banawa Selatan Kabupaten Donggala, J Pembangunan Agribisnis 2(1): 32-39 Kudsiah, H., Rahim, S. W., Rifa’i, M. A., & Arwan. (2018). Demplot Pengembangan Budidaya Kepiting Cangkang Lunak Di Desa Salemba, Kecamatan Ujung Loi, Kabupaten Bulukumba Sulawesi Selatan. Jurnal Panrita Abdi Universitas Hasanuddin, 2(2), 151–164. Retrieved from https://journal.unhas.ac.id/index.php/panritaabdi/issue/view/518 Megawati, S. (2021). Pengembangan Sistem Teknologi Internet of Things Yang perlu dikembangkan Negara Indonesia. Journal Information Engineering and Educational Technology (JIEET) 5(01): 19-26. Rifai, M. A., Candra, Muzdalifah, & Kudsiah, H. (2020). Pemberdayaan Istri Kelompok Pembudidaya Ikan Patin dengan Pengembangan Produk Fillet Empowerment for the Housewives of Patin Fish Farmers by Developing Fillet Products. Panrita Abdi, 4(3), 369–379. Supriharyono, 2000. Pelestarian dan Pengelolaan Sumberdaya Alam di Wilayah Pesisir Tropis. PT Gramedia Pustaka Utama, Jakarta.